2015
DOI: 10.1177/1090198115599397
|View full text |Cite
|
Sign up to set email alerts
|

Increases in Network Ties Are Associated With Increased Cohesion Among Intervention Participants

Abstract: Objective Many behavior change programs are delivered in group settings to manage implementation costs and to foster support and interactions among group members to facilitate behavior change. Understanding the group dynamics that evolve in group settings (e.g., weight management, Alcoholics Anonymous) is important, yet rarely measured. This paper examined the relationship between social network ties and group cohesion in a group-based intervention to prevent obesity in children. Method The data reported are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 33 publications
0
29
0
Order By: Relevance
“…These findings support earlier longitudinal research showing an association between the number of ties (degree) and perceived group cohesion. 31 Although the shared variance between our SNA-derived metrics and self-report measures was modest (ranged from .04 to .12), the empirical overlap between the SNA-derived metrics and self-report measures provides some evidence that the SNA metrics are detecting important structural features of a team's social network. 19 Our third aim concerned whether players reported similar levels of support for the reporting of concussion symptoms, or whether their perception of support differed by their social position on the team.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…These findings support earlier longitudinal research showing an association between the number of ties (degree) and perceived group cohesion. 31 Although the shared variance between our SNA-derived metrics and self-report measures was modest (ranged from .04 to .12), the empirical overlap between the SNA-derived metrics and self-report measures provides some evidence that the SNA metrics are detecting important structural features of a team's social network. 19 Our third aim concerned whether players reported similar levels of support for the reporting of concussion symptoms, or whether their perception of support differed by their social position on the team.…”
Section: Discussionmentioning
confidence: 85%
“…One of the documented advantages of using social network analysis is that it allows the simultaneous examination of team social structure and team members' self-report measures. 31 Our second aim capitalized on this dimension of SNA analysis and examined whether SNA-derived metrics were related to players' self-reported levels of football identity, team cohesiveness, and team belonging. Our exploratory analyses found that SNA measures of popularity (eigenvector centrality), connectedness (degree), and brokering (betweenness) were differentially associated with self-reported measures of belonging, cohesion, and football identity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…49 Social integration, or connectedness, is a very important network characteristic that can influence health and the impact of health-related interventions. 50 This can create a social environment that is conducive to making healthier choices, enhancing medication adherence, and improving retention in care, 51 thereby maximizing the intervention's effectiveness.…”
Section: Methodsmentioning
confidence: 99%
“…Reported strengths and limitations of the application of SNA Table 3 provides an overview of the reported strengths and limitations. Of the included studies, 6 studies (24%) reported only strengths in the application of SNA for developing and evaluating complex interventions, [31][32][33][34][35][36] 1 study (4%) reported a limitation, 37 4 studies (16%) did not report any strength or limitation, [38][39][40][41] and the remaining 14 studies (56%) reported strengths as well as limitations in the application of SNA. Reported limitations of the application of SNA were focused on the study design and data collection.…”
Section: Level Of Complexity Of Included Studiesmentioning
confidence: 99%